(Too) many policies under one roof? About the integration of competition law enforcement and sectoral regulation within one authority - Anna Piszcz (Market and Competition Law Review)
The traditional institutional model of a competition agency has assumed entrusting competition protection to a single authority. Over time, more and more often national competition authorities are being entrusted not only with competition enforcement but also with other functions (tasks). And the tendency to increasingly entrust competition authorities with additional roles not related to competition policy may seem worrying, as there may be a risk of pushing competition protection to the background. This article is going to reflect upon the relevant changes after the enlargement of the European Union (2004) and the current situation of selected competition authorities in this context. This contribution will explore the topic in relation to the main models of multifunctional competition authorities entrusted with sectoral regulation and examine authorities which combine competition enforcement with sectoral regulation in infrastructure industries. The article will also take into account that public enforcement of the prohibition of unfair trading practices provided for in Directive 2019/633 (“UTP Directive”), and limited to the agri-food market, was assigned to competition authorities (in line with the European Commission’s suggestion), which is the case of almost half of the EU Member States. It will attempt at the identification of advantages and disadvantages of entrusting competition authorities with additional sectoral regulation functions and discuss whether Directive 2019/1 (“ECN+ Directive”) may serve as a cure for disadvantages of adding not related objectives, such as overwhelming numbers of tasks and lacking resources, including human resources or a relatively small part of budget dedicated to competition enforcement. The research methods employed in this article include, first, a doctrinal legal method, second, systemic and teleological approaches, and, last, a comparative analysis.